Bilateral parotitis as a manifestation of autoimmune disease - T. V. Egorova; L. V. Malkova (LLC "Diagnostics and Vaccines", 2019)
The paper presents a clinical case of recurrent parotitis in a girl of 8 years during differential diagnosis, classified as Sjogren's syndrome in combination with autoimmune thyroiditis.